Faktor-Faktor Yang Mempengaruhi Kinerja Guru Smk Negeri Kelompok Pariwisata Di Daerah Istimewa Yogyakarta - Siti Zuhriyah (Universitas Alma Ata, 2015)
Abstract This research is aimed to prove whe of positive and significant influence from the teachers competence, job motivation teachers, job environment teachers, and principals leadership on the teachers performance of state vocational high school in Yogyakarta Special Region both partially and simultaneously. The population of this research were 169 teachers of state vocational high school productive program of turism group in Yogyakarta Special Region. The sample of this research were 118 teachers who represent each school proportionally. The sampling technique used was proportional random sampling. The instrument used in this research was questionnaire, which was used to measure teachers performance variable, teachers competence, job motivation teachers, job environment teachers, and principals leadership. The result of hypothesis test shows that: (1) the influence of the teacher’s competence on the teacher’s performance is positive and significant, (2) the influence of the job motivation on the teacher’s performance is positive and significant, (3) the influence the job environment on the teacher’s performance is positive and significant, (4) the influence of the principal’s leadership on the teacher’s performance is positive and significant, and (5) the teacher’s competence, job motivation, job environment, and principal’s leadership in aggregate have positive and significant influence on the teacher’s performance of vocational high school productive program of turism group in Yogyakarta Special Region. Keyword: competence, motivation, job environment, principal’s leadership, teacher’s performance